2016
DOI: 10.3390/toxins8020045
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Contamination in the EU Feed Supply Chain: A Focus on Cereal Byproducts

Abstract: Mycotoxins represent a risk to the feed supply chain with an impact on economies and international trade. A high percentage of feed samples have been reported to be contaminated with more than one mycotoxin. In most cases, the concentrations were low enough to ensure compliance with the European Union (EU) guidance values or maximum admitted levels. However, mycotoxin co-contamination might still exert adverse effects on animals due to additive/synergistic interactions. Studies on the fate of mycotoxins during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
224
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 269 publications
(247 citation statements)
references
References 127 publications
4
224
0
6
Order By: Relevance
“…Mycotoxins and other fungal metabolites represent the most insidious safety risks for cereal food and the feed supply chain (Pinotti et al, 2016). The occurrence of these compounds is a topic of great concern, because of the consequent negative health effect on humans and animals (Wild and Gong, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins and other fungal metabolites represent the most insidious safety risks for cereal food and the feed supply chain (Pinotti et al, 2016). The occurrence of these compounds is a topic of great concern, because of the consequent negative health effect on humans and animals (Wild and Gong, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of more fungal species in soya bean seed samples compared with fewer species, and less incidence in processed soya bean samples, can be attributed to practices involved with processing soya bean seeds. These practices which include de-hulling, frying and milling could have contributed to reducing fungal occurrence [19] [20]. The occurrence of different filamentous fungi in seeds could be attributed to, the predominantly hot and humid climatic weather of Nigeria [5] [6] [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins which are chemical compounds produced by fungi species, are able to withstand very high temperatures and pressure such that, they are not easily degraded or destroyed by cooking or baking [5] [18]. Despite their ability to withstand heat, it is reported that mycotoxin contamination in food commodities can be reduced by some practices such as dehulling, sorting, and cleaning [19] [20].…”
Section: Introductionmentioning
confidence: 99%
“…Fewer data are available regarding the distribution of other mycotoxins and modified mycotoxins in milling fractions [45,[142][143][144][145][146], but a similar scenario has been found, such as mycotoxins concentration in milling fractions intended for animal feed.…”
Section: Use Of Physical Chemical and Biological Decontaminating Mementioning
confidence: 99%